Diversity of Mangrove Crabs (Scylla spp.) in Bagan Deli Village, Medan Belawan District, North Sumatera - Persada, Andri Yusman; Putri, Kartika Aprilia; Andriani, Nadila (JURNAL BIOLOGICA SAMUDRA, 2025)
Mangrove crabs are important animals in mangrove ecosystems. This study aims to determine the diversity of mangrove crab species in Bagan Deli Village, Medan Belawan. Three species of mangrove crabs were found: Scylla olivacea (48 individuals), Scylla paramamosain (12 individuals), and Scylla tranquebarica (1 individual). The results showed low diversity index (0-0.69), low to high evenness index (0-0.62), and moderate to high dominance (0.58-1). This research is expected to be a learning material about mangrove crab species and sustainable mangrove forest utilization.